Processing and preservation technologies to enhance indigenous food sovereignty, nutrition security and health equity in North America - Heaney, Danielle; Padilla-Zakour, Olga I.; Chen, Chang (Frontiers in Nutrition, 2024)
Indigenous foods are carriers of traditional native North American food culture and living philosophy. They are featured by the wide varieties in fresh and processed forms, richness in nutrition, flavor, health benefits and diversity in origins, but are usually misunderstood or underrepresented in the modern food systems. Conventional processing and cooking methods are sometimes labor-intensive, less efficient and lack science-based guidelines to prevent unseen safety risks and food loss. Global and regional climate change have caused additional challenges to conventional cooking/processing, and increased native communities' reliance on externally produced foods, which have resulted in increasing nutritional unbalance and prevalence of diet-related health issues. Current and emerging technologies, such as storage and packaging, drying, safety processing, canning, pickling, and fermentation, which treat foods under optimized conditions to improve the safety and extend the shelflife, are increasingly used in current food systems. Therefore, exploring these technologies for indigenous foods offers opportunities to better preserve their nutrition, safety, and accessibility, and is critical for the sovereignty and independence of indigenous food systems, and sustainability of indigenous food culture. This mini-review focuses on identifying adoptable processing and preservation technologies for selected traditional indigenous foods in North America, summarizing education, extension, and outreach resources and discussing the current challenges and future needs critical to expanding knowledge about indigenous foods and improving food sovereignty, nutrition security, and health equity.